[M(ABC)6]錯体の配座解析 - 了爾; 御厨, 正博; 伊藤, 美咲; 安孫子, 誉晃; 脇, 克志; 﨑山, 博史 (Journal of Computer Chemistry, Japan, 2016)
Enumeration of the conformers and conformational analysis were successfully conducted for an octahedral [M(ABC)6] complex. In this report the methods and results were briefly described. In the enumeration, 7173 conformers were found by the computational group theory method, and among them, 130 conformers were found to have stable M(AB)6 cores of S6 symmetry. The structures of the 130 conformers of [Zn(DMSO)6]2+ (DMSO: dimethylsulfoxide) were optimized by the DFT method, and the most stable conformer was obtained.